Mode selection mechanism to enable effective device-to-device communication system over different environments - Zenalden, Feras; Hassan, Suhaidi; Habbal, Adib M. Monzer (2019)
Device-to-Device (D2D) communication is an important component of the 5G mobile networks. D2D communication enables users to communicate either directly without network assistance or with minimum signalling information through a base station (BS). Hence, D2D communication can enhance system capacity, increase spectral efficiency, improve throughput and reduce latency. One of the main challenges in D2D communications that when a potential D2D pair can switch between direct and conventional cellular communications, there lies a challenge in identifying D2D mode selection between communicating devices (i.e. a D2D pair). This paper aims to evaluate the mode selection mechanism in different environments (indoor, outdoor). The mode selection mechanism is proposed using multi-criteria for decision-making technique, the mode selection mechanism based on Simple Additive Weighting (SAW) algorithm is used to wisely connect and switch between the available modes. The evaluation of the proposed mechanism for indoor environment and outdoor environment shows better performance based on user preferences.